SUSTAINABLE HR PRACTICES THROUGH INCLUSIVE TALENT DEVELOPMENT IN SHARIA BANKING - Setiawati, Anindya Prastiwi; Mujanah, Siti; Sumiati, Sumiati (UTSAHA: Journal of Entrepreneurship, 2024)
Sharia banking has been challenged to create sustainable human resource management that meets Islamic principles. The need for inclusive talent management is becoming increasingly important to support operational sustainability and fairness within the organization. Therefore, this research is conducted to examine inclusive talent development as a key aspect of talent management for achieving sustainable human resources in Sharia banking practices. This research uses a qualitative case study method, with the findings presented as propositions. Data was collected through interviews and document analysis. The research shows that inclusive talent development not only helps individuals grow but also plays a key role in keeping talent within the organization. This includes identifying talent, developing technical and general skills, and using retention strategies like clear career paths, promotions, and fair compensation based on position. These findings highlight a strategic approach to sustainable HR management in sharia banking, where talent development fosters a supportive, inspiring work environment that helps retain employees and ensures long-term success for the organization.